Low WT1 transcript levels at diagnosis predicted poor outcomes of acute myeloid leukemia patients with t(8;21) who received chemotherapy or allogeneic hematopoietic stem cell transplantation. Issue 1 (December 2016) - Qin, Ya-Zhen; Wang, Yu; Zhu, Hong-Hu; Gale, Robert; Zhang, Mei-Jie; Jiang, Qian; Jiang, Hao; Xu, Lan-Ping; Chen, Huan; Zhang, Xiao-Hui; Liu, Yan-Rong; Lai, Yue-Yun; et al.
Abstract Background Acute myeloid leukemia (AML) with t(8;21) is a heterogeneous disease. Identifying AML patients with t(8;21) who have a poor prognosis despite achieving remission is important for determining the best subsequent therapy. This study aimed to evaluate the impact of Wilm tumor gene-1 (WT1 ) transcript levels and cellular homolog of the viral oncogenev -KIT receptor tyrosine kinase (C -KIT ) mutations at diagnosis, andRUNX1 -RUNX1T1 transcript levels after the second consolidation chemotherapy cycle on outcomes. Methods Eighty-eight AML patients with t(8;21) who received chemotherapy only or allogeneic hematopoietic stem cell transplantation (allo-HSCT) were included. Patients who achieved remission, received two or more cycles of consolidation chemotherapy, and had a positive measureable residual disease (MRD) test result (defined as <3-log reduction inRUNX1 -RUNX1T1 transcript levels compared to baseline) after 2–8 cycles of consolidation chemotherapy were recommended to receive allo-HSCT. Patients who had a negative MRD test result were recommended to receive further chemotherapy up to only 8 cycles.WT1 transcript levels andC -KIT mutations at diagnosis, andRUNX1 -RUNX1T1 transcript levels after the second consolidation chemotherapy cycle were tested. Results Patients who had aC -KIT mutation had significantly lowerWT1 transcript levels than patients who did not have aC -KIT mutation (6.7% ± 10.6% vs. 19.5% ± 19.9%, P  < 0.001). LowWT1 transcript levels (≤5.0%) but notC -KIT mutation at diagnosis, a positive MRD test result after the second cycle of consolidation chemotherapy, and receiving only chemotherapy were independently associated with high cumulative incidence of relapse in all patients (hazard ratio [HR] = 3.53, 2.30, and 11.49; 95% confidence interval [CI] 1.64–7.62, 1.82–7.56, and 4.43–29.82;P  = 0.002, 0.034, and <0.001, respectively); these conditions were also independently associated with low leukemia-free survival (HR = 3.71, 2.33, and 5.85; 95% CI 1.82–7.56, 1.17–4.64, and 2.75–12.44;P  < 0.001, 0.016, and <0.001, respectively) and overall survival (HR = 3.50, 2.32, and 4.34; 95% CI 1.56–7.82, 1.09–4.97, and 1.98–9.53;P  = 0.002, 0.030, and <0.001, respectively) in all patients. Conclusions Testing forWT1 transcript levels at diagnosis in patients with AML and t(8;21) may predict outcomes in those who achieve remission. A randomized study is warranted to determine whether allo-HSCT can improve prognosis in these patients.